Atrial fibrillation (AF) in endurance athletes: A complicated affair - Stergiou, D.; Duncan, E. (Current Treatment Options in Cardiovascular Medicine, 2018)
Purpose of review: A complex relationship exists between exercise and atrial fibrillation (AF). Moderate exercise reduces AF risk whereas intense strenuous exercise has been shown to increase AF burden. It remains unclear at which point exercise may become detrimental. Overall, endurance athletes remain at lower cardiovascular risk and experience fewer strokes. The questions that arise therefore are whether AF is an acceptable byproduct of strenuous exercise, whether athletes who experience AF should be told to reduce exercise volume and how should they be managed. This review aims to critically review the literature and advise on how best to manage athletes with AF. Recent findings: Emerging evidence suggests that female athletes may exhibit lower risk of AF, but data is limited in female endurance athletes. Summary: AF is more prevalent in endurance athletes, particularly men and those who competed at a young age. Data is lacking in females and ethnic minorities. Current evidence suggests that treatment options for AF in athletes are similar to those used in the general population; however, medical therapy may be poorly tolerated. Catheter ablation is effective and can allow return to full competition.